Rapid Optimization of Dielectric Rod Arrays for Microwave Radiation Shaping Applications - Yazar, Sirin; Hatipoglu, M. Enes; Eris, Ozgur; Ergul, Ozgur; Dikmen, Fatih (IEEE, 2023)
Well-designed arrangements of arrays of circular lossy dielectric rods with finite lengths have been exploited to obtain proper radiation patterns for microwave applications. Accelerated three-dimensional (3D) numerical modeling of such radiation mechanisms via the multilevel fast multipole algorithm (MLFMA) is suitable for well-matched results with real-life experiments. Enabling rigorous and accurate analyses of the corresponding problems, MLFMA, has been observed to provide quasi-optimal designs within a reasonable period of time, when this algorithm is efficiently combined with genetic algorithms (GAs). However, as shown in this contribution, the corresponding two-dimensional (2D) multiple scattering modeling via a well-conditioned version of the T-matrix method provides a much faster tool for GAs to optimize radiation patterns for a goal set on the central cross section plane of the rod arrays. Optimized geometries obtained using a combination of the 2D solver and GAs have been validated by using a 3D solver based on MLFMA to demonstrate the feasibility of the approach.
IEEE MTT-S International Conference on Numerical Electromagnetic and Multiphysics Modeling and Optimization (NEMO) -- JUN 28-30, 2023 -- Winnipeg, CANADA
Keywords: Genetic algorithms; T-matrix method; multilevel fast multipole algorithm; microwave applications